2019
DOI: 10.1038/s41418-018-0235-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of the LncRNA-FA2H-2-MLKL pathway in atherosclerosis by regulation of autophagy flux and inflammation through mTOR-dependent signaling

Abstract: Atherosclerosis is a progressive, chronic inflammation in arterial walls. Long noncoding RNAs (lncRNAs) participate in inflammation, but the exact mechanism in atherosclerosis is unclear. Our microarray analyses revealed that the levels of lncRNA-FA2H-2 were significantly decreased by oxidized low-density lipoprotein (OX-LDL). Bioinformatics analyses indicated that mixed lineage kinase domain-like protein (MLKL) might be regulated by lncRNA-FA2H-2. In vitro experiments showed that lncRNA-FA2H-2 interacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 47 publications
2
85
0
Order By: Relevance
“…FA2H-2 was also reduced in ox-LDL treated ECs or SMCs and could inhibit the activity of NF-κB, which plays an important role -n inflammation. In addition, FA2H-2 also repressed autophagy by inhibiting mixed lineage kinase domain-like protein (MLKL), which can activate the inflammasome via the p38 MAPK/PI3K pathway (93). FA2H-2 could regulate ox-LDL induced inflammation, involved in the development of atherosclerosis.…”
Section: Lncrna Fa2h-2mentioning
confidence: 99%
“…FA2H-2 was also reduced in ox-LDL treated ECs or SMCs and could inhibit the activity of NF-κB, which plays an important role -n inflammation. In addition, FA2H-2 also repressed autophagy by inhibiting mixed lineage kinase domain-like protein (MLKL), which can activate the inflammasome via the p38 MAPK/PI3K pathway (93). FA2H-2 could regulate ox-LDL induced inflammation, involved in the development of atherosclerosis.…”
Section: Lncrna Fa2h-2mentioning
confidence: 99%
“…For example, chen et al (11) demonstrated that knockdown of lncRNA growth arrest specific 5 suppresses atherogenesis by regulating the apoptosis of macrophages and endothelial cells via exosomes. in addition, lncrna-Fa2H-2 has been shown to alleviate the inflammatory response, which acts as an independent risk factor of atherogenesis induced by oxidized low-density lipoprotein (ox-ldl), via the induction of the autophagic flux (12). These previous studies showed that lncrnas act as promoting or inhibiting factors in aS development.…”
Section: Introductionmentioning
confidence: 96%
“…However, MLKL and Rab7 were not co-localized under acetylated LDL conditions, which is known to be less inflammatory than oxidized and aggregated LDL, and where fewer MLKL positive punctate structures were seen. Others have shown in vitro that MLKL inhibits autophagic flux in non-macrophage cell types, therefore it is unlikely that the absence of MLKL would lead to reduced autophagy of lipid droplets 24,25 . Rather, we hypothesize that MLKL regulates the tethering of Rab7-positive late endosomes and/or multivesicular bodies (MVBs) at ER-endosome contact sites, possibly via ESCRT machinery to regulate lipid droplet mobilization 14,19 .…”
Section: Discussionmentioning
confidence: 99%